2016
DOI: 10.1186/s12889-016-3587-7
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of implementing a large scale larviciding campaign against malaria in rural Burkina Faso – lessons learned and recommendations derived from the EMIRA project

Abstract: BackgroundRecent malaria control and elimination attempts show remarkable success in several parts of sub-Saharan Africa. Vector control via larval source management represents a new and to date underrepresented approach in low income countries to further reduce malaria transmission. Although the positive impact of such campaigns on malaria incidence has been researched, there is a lack of data on which prerequisites are needed for implementing such programs on a routine basis on large scale. Our objectives ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Other evaluations of malarial larviciding interventions have similarly found that these programs are highly complex and context-specific, requiring acute attention to detail. For large-scale larviciding programs, coordination with Ministries of Health, local community leaders, and research groups is essential to achieve widespread success in rolling out activities [ 21 ]. Although this requires extensive planning and arrangement in advance, the day-to-day activities of larviciding teams and supervisors must be somewhat flexible to account for unanticipated changes such as weather events or issues with machine sprayers [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other evaluations of malarial larviciding interventions have similarly found that these programs are highly complex and context-specific, requiring acute attention to detail. For large-scale larviciding programs, coordination with Ministries of Health, local community leaders, and research groups is essential to achieve widespread success in rolling out activities [ 21 ]. Although this requires extensive planning and arrangement in advance, the day-to-day activities of larviciding teams and supervisors must be somewhat flexible to account for unanticipated changes such as weather events or issues with machine sprayers [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For large-scale larviciding programs, coordination with Ministries of Health, local community leaders, and research groups is essential to achieve widespread success in rolling out activities [ 21 ]. Although this requires extensive planning and arrangement in advance, the day-to-day activities of larviciding teams and supervisors must be somewhat flexible to account for unanticipated changes such as weather events or issues with machine sprayers [ 21 , 22 ]. The need for close supervision of larviciding staff to ensure quality control of the intervention, coupled with budgetary concerns and other factors, demonstrates the high level of complexity involved in implementing these programs.…”
Section: Discussionmentioning
confidence: 99%
“…It was a community-based intervention trial using Bti as a larvicide, and examined the added health benefit of biological larviciding in rural Burkina Faso. Methods have been described in detail elsewhere [ 22 24 ]. In brief, each of the 127 NHD rural villages were assigned to one of three study arms: Bti -based LSM in all breeding sites within and around villages (100% treatment arm); selective treatment of breeding sites with the assumed highest vector larvae productivity (50% treatment arm) [ 25 , 26 ] and an untreated control group.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these malaria control o cials particularly MFPs and VSOs reported to have attended at least one theoretical training on larviciding. However, those training proved to be insu cient as acquiring necessary expertise would require practical, "on the job" training rather than a presentation of theoretical principles [42]. No formal training to the actual implementers (i.e.…”
Section: Discussionmentioning
confidence: 99%